Populations of dwarf araucaria (Araucaria araucana) in the Nahuelbuta coastal range, Chile - Donoso, Claudio; González, Mauro E.; Cortés, Marco; González, Conrado; Donoso, Pablo; Hernández, Marcelo (Bosque (Valdivia), 2008)
Araucaria araucana (araucaria or pehuén) can normally reach > 20 m in height in most sites where it grows. However, two dwarf populations of A. Araucana were found at the top of the Nahuelbuta coastal range. This study had the goal of characterizing the structure, composition, ages and chemical and physical soil properties of both populations. These populations are dominated by A. araucana, with Nothofagus dombeyi as the main associated species. Dwarfism is clear in both species. Individuals of A. araucana rarely exceeded 10 m in height with a high diameter/height relationship compared with similarly-aged normal trees. The diameter annual growth is lower than 0.12 cm for trees 300 years in age and basal diameters of 36 cm. The presence of short stems and extended and fine branches, like spider legs, confirms the dwarf features of the A. araucana trees. In N. dombeyi 36 to 37 years in age the diameter annual growth is between 0.26 and 0.27 cm, where most individuals (60-75%) present basal diameters lower than 15 cm and heights between 1 and 6.5 m. The location of these populations at the top of the Nahuelbuta coastal range over 1,000 m and openly exposed to the Pacific ocean results from extreme weather conditions that combined with poor and thin soils determine the low tree growth, reduced size and tortuous shapes of trees.